Market Potential of Northwest Russia for Telemedicine Applications - Miettinen, Raimo (2008)
The level of health care in Russia is mostly still below the western standards, but lately it has been developing quite positively. Many ICT solutions (telemedicine applications) have been developed for health care in Finland, but since the domestic market is so small, it’s necessary to expand to foreign markets to make the Finnish R&D projects more profitable. Telemedicine applications are not yet widely used in Russia, but since the health care system is going through fast changes, leapfrog effects can be expected and new modern applications and technologies will be implemented. This will open numerous business opportunities for Finnish technology developers. This thesis aims to be the first evaluation of the market and form an outlook of the health care system and telemedicine applications already utilized in Russia. The results of this study can be used for focusing further research ultimately aiming at technology implementation. The study showed that there is potential for many types of telemedicine solutions, e.g. electronic patient records and home monitoring systems; providing that further research in this field is needed. Venäjän terveydenhuollon taso on edelleen länsimaista tasoa alhaisempi, mutta viime aikoina maan terveydenhuolto on kehittynyt positiivisesti. Suomessa on kehitetty monia ICT-sovelluksia terveydenhuollon tarpeisiin, mutta koska kotimaiset markkinat ovat niin pienet, on tarpeen kartoittaa sovellusten kaupallistamismahdollisuuksia ulkomailla. Telelääketieteen sovelluksia ei Venäjällä ole vielä laajalti käytössä. Sektorin jatkuva positiivinen kehitys vaatii prosessien uudelleenarviointeja - uusia teknologioita ja sovelluksia otetaan käyttöön tukemaan hoito- ja hallintoprosesseja. Tämä avaa lukuisia mahdollisuuksia suomalaisille alan teknologiayrityksille. Tämä DI-työ on ensimmäinen katsaus näille markkinoille ja siinä luodaan yleiskuvaus Venäjän terveydenhuollosta sekä jo käytössä olevista telelääketieteen sovelluksista. Tämän työn tuloksia voidaan käyttää pohjana suunniteltaessa ...